Tribological properties of MIM manufactured copper alloys. (March 2014) - Jisa, R.; Laumann, S.; Cihak-Bayr, U.; Tomastik, C.; Eberle, R.; Keppeler, M.; Hofmann, U.; Franek, F.
<x content-type="archive" xml:space="preserve">Abstract</x> Metal injection moulding (MIM) offers advantages for mass production of components which may be subjected to tribological load. Obviously, MIM processing influences material and thus tribological properties. Contrariwise, it is possible to gain specific favourable tribological properties by MIM. MIM manufactured CuNi9Sn6 and CuSn8 based on commercial feedstocks were subject of investigations and were compared to conventionally manufactured materials. For tribological testing, an SRV tribometer in a modified set-up was applied. MIM-CuNi9Sn6 appears promising in terms of low friction and wear, especially if heat treated after MIM production. This work compares tribometrological results and the related microstructures.